Optimized Design of a Wedge-type Overrunning Clutch Structural Parameter - Wang Honglin; Su Yi; Guo Xiancheng; Chen Yuanwen; Huang Shuai (Jixie chuandong)
According to the requirements of overrunning coupler to the floating micro wave power generating device,the friction loss rate of wedge- type overrunning clutch at overrunning states is analyzed and the parameters mathematical models of the wedge- type overrunning clutch are built. Taking the minimize volume and the friction loss rate as design aims,with the strength and the sizes of various parts to be the constraint conditions,the optimization model is established,and the mathematical model is solved by using the MATLAB. Finally,compared with the conventional design parameters,the results show that the volume of the optimization design is only71. 99% of the conventional design,and the friction loss rate of the optimization design decreased 2. 26 percentage,which can makes the floating power generating device more compact,lighter and more efficient.